Willingness to work as a predictor of human-agent team success - Gurney, Nikolos; Pynadath, David V.; Miller, John H. (Frontiers in Computer Science, 2025)
Research shows that the effectiveness of human-agent teams depends heavily on human team members' prior experiences, whether from direct teaming activities or relevant domain knowledge. While researchers have proposed various mechanisms to explain this relationship, we present a simpler alternative explanation: experience serves primarily as an indicator of a person's fundamental willingness to engage in teaming tasks. We introduce a measure called “willingness to work” that quantifies this underlying disposition. Our empirical analysis demonstrates that this straightforward metric robustly predicts human-agent team performance. Beyond its practical value as a predictive tool, this reconceptualization of the experience-performance relationship necessitates a fresh examination of existing findings in the field. The results suggest that a team member's basic willingness to invest effort may be more fundamental to success than previously recognized mechanisms.